Predictive value of circulating galectin-3 in patients with multiple myeloma in remission - B. B. Samura (Zaporožskij Medicinskij Žurnal)
Objective. We aimed to evaluate the prognostic value of circulating galectin-3 for cumulative survival in patients with multiple myeloma in full or partial remission.